Evaluation of swiss chard (Beta vulgaris L. ssp. cicla) physiological and qualitative responses to water deficit and salicylic acid treatment - Giulia Franzoni; Davide Guffanti; Antonio Ferrante; María Jesús Cejudo-Bastante; Francisco J. Rodríguez-Pulido; Belén Gordillo; Giacomo Cocetta (Journal of Agriculture and Food Research)
Swiss chard is a rich dietary source of bioactive betalain pigments responsible of the red colour of the plant's organs and of phenolic compounds having recognized antioxidant properties. Vegetable colour and appearance, as the first characteristics perceived, are important quality attributes that influence the consumer's acceptance. Currently, elicitation based on growth plant regulator supply is considered in most cases a useful strategy to enhance the sensorial and nutritional value of dietary plants. Thus, this study aimed to assess the impact of salicylic acid application on Swiss chard (Beta vulgaris L. ssp. cicla) grown, isolated and under water shortage, in relation to physiological and qualitative parameters throughout cultivation and at harvest. Different effects were observed depending on the type and interaction of stress-inducing treatments. Positive effects consisted in highest chlorophyll (r.u.) (+19–40 %) carotenoids (+34–48 %), and phenolic contents (+2–42 %) in leaves when treatments were applied isolated or in combination, which also led to high sugar levels in plants (up to 380 %). Negative effects included the reduction of biomass production (−40 %), leaf size (−38 %), and betalain content (-7-27 %), especially with combined treatments. Nitrate accumulation was not affected but salicylic acid induced a reduction in proline levels probably due to increased carbohydrate and nitrate metabolisms in regulating water deficit.